Influence of Metal Ions on Microtubules as a Possible Mechanism of Pathogenesis of Alzheimer′s Disease - Shevtsov, P.N.; Shevtsova, E.F.; Bachurin, S.O. (Biomedical Chemistry: Research and Methods, 2018)
The article provides an overview of our own results of comparative study of influence of ions of iron, zinc and aluminium on the structure of microtubules from tubulin and microtubules associated proteins of rat brain with data on the structure of microtubules from tubulin and microtubules associated proteins from the brain of patients with Alzheimer′s disease (AD). A significant decrease in the amount of soluble tubulin was found in the postmortem brain of AD patients in comparison with the control group in the hippocampus, frontal cortex and substantia nigra, but not in the inferior olive. In vitro polymerization of tubulin and microtubules associated proteins from the brain of AD patients and electron micrographs of microtubules were obtained. The assembly of microtubules from brains of AD patients is disrupted, resulting in defective structures. On the other hand, the study of the influence of Al3+, Fe3+, Zn2+ on the microtubules from rat brains tubulin and microtubules associated proteins assembly and structure has shown that all studied metals are able to reduce the amount of microtubules and induce the assembly of anomal structures. According to the degree of the destructive effect on the microtubules and, accordingly, the possible significance in the pathogenesis of Alzheimer disease, metal ions can be arranged in the following sequence Al3+ > Zn2+ > Fe3+. Moreover, phosphorylation of tubulin and microtubules associated proteins in the presence of aluminum ions to the greatest extent reflects the phosphorylation of these proteins at AD. Comparison of data on the structure of microtubules after their assembly from brains of AD patients tubulin and microtubules associated proteins from brains of AD patients, and from the brain of rats, but in the presence of metal ions, confirm the conclusion about the possible role of the metals in the AD etiopathogenesis.